2017
DOI: 10.3390/w9110817
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Composition and Depth Affect Soil Moisture Behavior and Plant-Soil Relationship on Mediterranean Extensive Green Roofs

Abstract: Abstract:The Mediterranean basin is extremely vulnerable to climate change, and one of the areas most impacted by human water demand. Yet the green roofs increasingly created both for aesthetic reasons and to limit pollution and urban runoff are themselves very water-demanding. Successful green roof installation depends on the establishment of the vegetation, and the substrate is the key element: it conserves water, and provides the nutrients and physical support indispensable for plant growth. Since typical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
(62 reference statements)
0
8
1
Order By: Relevance
“…The results of the t-test indicate no statistically significant differences between the two groups (p-value = 0.548), obtaining similar results as in some previous studies [38,42,43], which have stated that vegetation does not have a clear effect on water retention efficiency for GRs. The previous result contrasts with that of Chenot et al [17] who concluded that vegetated coverage does have an influence on water retention even though substrate composition and depth have a greater effect. This disagreement may be the result of not considering the hydrological conditions.…”
Section: Effect Of Vegetation On Water Retention Efficiencycontrasting
confidence: 86%
“…The results of the t-test indicate no statistically significant differences between the two groups (p-value = 0.548), obtaining similar results as in some previous studies [38,42,43], which have stated that vegetation does not have a clear effect on water retention efficiency for GRs. The previous result contrasts with that of Chenot et al [17] who concluded that vegetated coverage does have an influence on water retention even though substrate composition and depth have a greater effect. This disagreement may be the result of not considering the hydrological conditions.…”
Section: Effect Of Vegetation On Water Retention Efficiencycontrasting
confidence: 86%
“…Chenot et al [88] assessed the role of substrate thickness and composition in maintaining the moisture necessary for good vegetation cover. The authors mixed fine elements (clays and silts) with coarse elements (pebbles of all sizes) with the aim of allowing typical pioneer Mediterranean vegetation communities to be maintained without human intervention (no watering, mechanical or chemical weeding).…”
Section: Possible Materials Selectionmentioning
confidence: 99%
“…For example, 3-5 years after planting, a roof subject to average Swiss rainfall conditions with a ≥10-cmthick substrate is likely to support a meadow-like plant community (Nagase and Dunnett 2013). Also, the variability of substrate thickness, particle size and soil type and the percentage of organic matter may strongly influence plant diversity (Chenot et al 2017;Dunnett et al 2008).…”
Section: The Role Of Vegetation Patterns On Green Roofsmentioning
confidence: 99%